ChemInform Abstract: Polyketides from the Mangrove‐Derived Endophytic Fungus Acremonium strictum. Issue 47 (6th November 2014) - Hammerschmidt, Lena; Debbab, Abdessamad; Ngoc, Tu Duong; Wray, Victor; Hemphil, Catalina Perez; Lin, WenHan; Broetz‐Oesterhelt, Heike; Kassack, Matthias U.; Proksch, Peter; Aly, Amal H.
Abstract The absolute configuration of compound (I) is determined using a modified Mosher method.